Building an Original and Internationally Standardized Public Health System in the Kingdom of Yugoslavia - Dugac, Željko (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2024)
This paper analyzes the key processes involved in establishing the public health system in the Kingdom of Serbs, Croats, and Slovenes (later the Kingdom of Yugoslavia), drawing upon existing scholarly studies and relevant archival sources. In the aftermath of World War I, the nascent state was confronted with numerous public health challenges. The establishment of the Ministry of Public Health marked the beginning of efforts to address these issues, as the Ministry assumed responsibilities over healthcare, medicine, veterinary medicine, pharmacy, and military health. This initiative included the enactment of necessary legal regulations, the creation of social medical institutions, and the regulation of medical personnel training, thereby laying the groundwork for a new approach to public health. The Ministry spearheaded reforms in the organization of health services, encompassing the establishment of new healthcare institutions, the creation of an innovative educational system, and the implementation of health programs and competencies designed to address both crisis situations and ongoing healthcare needs. Concurrently, the Ministry launched various preventive and social programs, as well as comprehensive health education initiatives, aimed at enhancing public awareness of hygiene and healthy behaviors. Additionally, significant efforts were made to establish enduring conditions for the integration of new scientific knowledge into daily life. All these programs were unified by a common ideological principle that posited that medicine, healthcare, and scientific advancements must serve the broader society, ensuring equal access for all community members. These initiatives were undertaken under the auspices of the Hygiene Department of the Ministry of Public Health, led by Dr. Andrija Štampar, an internationally recognized public health expert. The development of this public health system was further supported by professional and financial assistance from international organizations, including the Health Organization of the League of Nations and the Rockefeller Foundation. This collaborative effort resulted in the creation of a public health system that was both original and internationally standardized.